2002
DOI: 10.1128/jvi.76.21.11113-11122.2002
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirements for COPI Coats in Formation of Replication Complexes among Three Genera of Picornaviridae

Abstract: Picornavirus RNA replication requires the formation of replication complexes (RCs) consisting of virusinduced vesicles associated with viral nonstructural proteins and RNA. Brefeldin A (BFA) has been shown to strongly inhibit RNA replication of poliovirus but not of encephalomyocarditis virus (EMCV). Here, we demonstrate that the replication of parechovirus 1 (ParV1) is partly resistant to BFA, whereas echovirus 11 (EV11) replication is strongly inhibited. Since BFA inhibits COPI-dependent steps in endoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
135
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(139 citation statements)
references
References 54 publications
4
135
0
Order By: Relevance
“…The authors found that viral vesicles bud from the ER but do not fuse with the ER/ Golgi intermediate complex and suggested that the cellular COPII machinery participates in the induction of vesicles suitable for poliovirus replication. However, the inhibition of poliovirus and rhinovirus RNA replication by brefeldin A directly contradicts this hypothesis (20,30). Brefeldin A inhibits formation of COPI but not COPII vesicles.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The authors found that viral vesicles bud from the ER but do not fuse with the ER/ Golgi intermediate complex and suggested that the cellular COPII machinery participates in the induction of vesicles suitable for poliovirus replication. However, the inhibition of poliovirus and rhinovirus RNA replication by brefeldin A directly contradicts this hypothesis (20,30). Brefeldin A inhibits formation of COPI but not COPII vesicles.…”
Section: Discussionmentioning
confidence: 77%
“…The mechanisms of vesicle production and replication complex formation in picornavirus-infected cells have not been defined. The vesicles, which are induced by the synthesis of 2BC, 2C, and 3A proteins, may initially form as COPII vesicles (57), autophagic vesicles (59,61), or COPI vesicles (30). Regardless of the origin of picornavirus-induced vesicles, some viral proteins must interact with host cell proteins to generate the membrane alterations that occur in the cell and lead to the formation of replication complexes.…”
mentioning
confidence: 99%
“…In addition, we tested whether mengovirus, a member of the cardiovirus genus known to be resistant to BFA (7,9), is sensitive to treatment with GCA. BGM cells (CVB3/ EV71), HeLa cells (CVA21), and BHK-21 cells (mengovirus) were infected with the different viruses and incubated in the presence or absence of GCA.…”
Section: Vol 84 2010 Effects Of Gbf1 Inhibitors On Enterovirus Replmentioning
confidence: 99%
“…Another possibility is that tyrosine 78 could be involved in crosstalking to cellular host factors that are essential for virus assembly. Several host proteins such as COPI and COPII factors have been reported to be involved in poliovirus production and formation of replication complexes in picornavirus (Rust et al, 2001;Gazina et al, 2002).…”
Section: Discussionmentioning
confidence: 99%